A novel approach for sizing and optimization of hybrid solar-PV, biogas-generator, and batteries system for rural electrification: case study - Cheibany Cheikh Ebeya; Mohamed Mahmoud Ali; Mamoudou Ndongo; Ahmed Sidibba; Kaan Yetilmezsoy; Emel Kiyan; Boudy Bilal; Eslemhoum Jedou; Halima Maiguizo Diagne; Issakha Youm (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A new approach for sizing a hybrid solar-PV-battery and biogas generator for power generation was suggested in this study, based on the variation of energy resources and the load profile. Biogas has enormous potential and numerous economic and social advantages. In this respect, the monthly solar radiation, temperature, and biogas produced from biomass resources were used as model inputs. This study considers the total annualized of the components for the feasibility analysis. HOMER Pro® software-based outcomes in the proposed methodology revealed that the proposed solar biogas hybrid system was sufficient to meet the load requirements of the village (Ain Farba village in the Hodh El Gharbi area located in the northeast of the Mauritania country) with a net present cost over the 25-year lifespan of 61,144 $ and the energy cost was determined to be 0.0473 $/kWh.